Рецензия на книгу "Algae of Ukraine: Diversity, nomenclature, taxonomy, ecology and geography" под ред. П.М. Царенко - Паламарь-Мордвинцева, Г.М. (Альгология, 2006)
Algae of Ukraine: Diversity, Nomenclature. Taxonomy, Ecology and Geography / P.M. Tsarenko, S.P. Wasser, E. Nevo (eds.). Vol. 1. - Ruggell: A.R.A. Gantner Verlag K.-G., 2006.-713 p.